CURRENT PROBLEMS OF FEDERAL TAXATION. - Buckley, David A. (The Accounting Review, 1936)
The article discusses current problems of tax administration and procedures in the U.S. The article suggests certain ways to bring awareness in these taxpayers. These include advice to taxpayers as to the effect of proposed transactions, advice and assistance to taxpayers in the recording of the business facts upon which tax liability is predicated, advice and assistance to taxpayers in the preparation and filing of returns, conferences with revenue agents in connection with the examination of returns, filing of claims for refund, filing letters of protest, attendance at hearings and the submission of evidence, conduct of appeals to the United States Board of Tax Appeals, including the filing of a petition, the preparation of evidence, the trial of the issues, the preparation and filing of briefs, and such motion practice as may be necessary, suits in the District Courts and Court of Claims and appeals to Circuit Court of Appeals and Supreme Court. While knowledge of the tax law and the regulations issued there under is essential throughout, however, in the earlier stages the matter is largely one of facts and therefore a matter of accounting, while in its final stages the matter becomes entirely one of law.